Analysis of a chitinase from EpapGV, a fast killing betabaculovirus - Salvador, Ricardo (2014)
The main function of baculoviral chitinase protein (V-CHIA) is to promote the final liquefaction of infected host larvae, facilitating the dispersion of occlusion bodies (OBs) in the environment. In this study, a v-chiA from Epinotia aporema Granulovirus (EpapGV) was identified and characterized. The 1,713 base pairs long open reading frame encodes a protein of 570 amino acids with a predicted molecular weight of 63 kDa. EpapGV V-CHIA sequence alignment resulted 62 % identical to Pieris rapae GV and Blastp search revealed a high conservation among all baculovirus chitinases. Amino acid sequence analysis indicated that the C-terminal KDEL present in most alphabaculovirus chitinases is absent in EpapGV V-CHIA, as well as in the rest of the betabaculoviruses. Phylogenetic analysis was performed with bacterial, lepidopteran, and baculoviral chitinase sequences available in databases. Using an AcMNPV bacmid (bApGOZA) a recombinant Ac-chiAEpapGV was obtained in order to overexpress EpapGV V-CHIA in cell culture. The presence of chitinase was detected in purified AcMNPV-chiAEpapGV OBs. Peritrophic membranes of Anticarsia gemmatalis larvae fed with recombinant OBs showed an altered structure. The results presented in this study show that EpapGV chitinase overexpression in recombinant baculovirus can cause association of this protein with OBs, and suggest that this could be used to evaluate the protein role in early stages of baculoviral infections.